2011
DOI: 10.1007/s12011-011-9224-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Serum Calcium and Magnesium Concentrations and Metabolic Syndrome Diagnostic Components in Middle-Aged Korean Men

Abstract: It is thought that calcium and magnesium may be related to metabolic disorders such as obesity and metabolic syndrome; however, to date, there have been few studies investigating the association between serum calcium and magnesium levels and metabolic syndrome in middle-aged male adults. We aimed to investigate the association between serum calcium and magnesium levels and metabolic syndrome in Korean middle-aged male adults. Study subjects included 213 men aged 30∼60 years. MetS risk score is determined by ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 40 publications
0
27
6
Order By: Relevance
“…Circulating lipid levels are also associated with serum calcium in cross‐sectional studies []. As previously described, their importance appears to be comparable to that of blood pressure.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Circulating lipid levels are also associated with serum calcium in cross‐sectional studies []. As previously described, their importance appears to be comparable to that of blood pressure.…”
Section: Discussionmentioning
confidence: 82%
“…This suggests that serum calcium might drive dyslipidaemia changes, but this finding was not confirmed in a randomized trial of this condition . Other studies have suggested associations of serum calcium with glucose metabolism and metabolic syndrome and with BMI , which might contribute to the calcium–cardiovascular relationship. Again, causality in these associations is unclear.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Mg and Ca are intimately related to each other and have been reported to collectively influence metabolic functions such as hypertension and insulin resistance [24][25][26] . Therefore, several studies have investigated the associations between levels of Mg and Ca with MetS together in adults [27,28] . Park et al [27] examined serum Ca and Mg concentrations in middle-aged Korean men and found the serum Ca was positively associated with MetS risk score, triglyceride (TG) and diastolic blood pressure (DBP), while serum Mg had no statistically significant association with MetS risk score but a negative association with serum glucose.…”
mentioning
confidence: 99%
“…Therefore, several studies have investigated the associations between levels of Mg and Ca with MetS together in adults [27,28] . Park et al [27] examined serum Ca and Mg concentrations in middle-aged Korean men and found the serum Ca was positively associated with MetS risk score, triglyceride (TG) and diastolic blood pressure (DBP), while serum Mg had no statistically significant association with MetS risk score but a negative association with serum glucose. However, results of another study conducted among the Korean population showed negative associations between both hair Mg and Ca concentrations with MetS [28] .…”
mentioning
confidence: 99%